Uptake and efficacy of bilateral risk reducing surgery in unaffected female BRCA1 and BRCA2 carriers. Issue 2 (10th February 2021) - Marcinkute, Ruta; Woodward, Emma Roisin; Gandhi, Ashu; Howell, Sacha; Crosbie, Emma J; Wissely, Julie; Harvey, James; Highton, Lindsay; Murphy, John; Holland, Cathrine; Edmondson, Richard; Clayton, Richard; et al.
Abstract : Background: Women testing positive for BRCA1/2 pathogenic variants have high lifetime risks of breast cancer (BC) and ovarian cancer. The effectiveness of risk reducing surgery (RRS) has been demonstrated in numerous previous studies. We evaluated long-term uptake, timing and effectiveness of risk reducing mastectomy (RRM) and bilateral salpingo-oophorectomy (RRSO) in healthy BRCA1/2 carriers. Methods: Women were prospectively followed up from positive genetic test (GT) result to censor date. χ² testing compared categorical variables; Cox regression model estimated HRs and 95% CI for BC/ovarian cancer cases associated with RRS, and impact on all-cause mortality; Kaplan-Meier curves estimated cumulative RRS uptake. The annual cancer incidence was estimated by women-years at risk. Results: In total, 887 women were included in this analysis. Mean follow-up was 6.26 years (range=0.01–24.3; total=4685.4 women-years). RRS was performed in 512 women, 73 before GT. Overall RRM uptake was 57.9% and RRSO uptake was 78.6%. The median time from GT to RRM was 18.4 months, and from GT to RRSO–10.0 months. Annual BC incidence in the study population was 1.28%. Relative BC risk reduction (RRM versus non-RRM) was 94%. Risk reduction of ovarian cancer (RRSO versus non-RRSO) was 100%. Conclusion: Over a 24-year period, we observed an increasing number of women opting for RRS. We showed that the timing of RRS remains suboptimal, especially in women undergoing RRSO. Both RRM and RRSO showed a significant effect on relevant cancer risk reduction. However, there was no statistically significant RRSO protective effect on BC.